The political women of Singapore : what does it take her to join politics? - Asrul, Ajriani (2016)
From the years 1970 to 1984, women were absent from the political ranks of government in Singapore. Since then, women have been elected in increasing numbers with each successive election. However, they remain the minority in Parliament despite making up half of the population. This exploratory study wishes to investigate the challenges that women in Singapore face in entering the political arena from the perspective of women who have participated in the political process. Through qualitative data, this study aims to demonstrate that cultural factors, above others, continue to plague the ambitions and desires of a political woman today who remains subjected to the same paternalistic and patriarchal norms that her predecessors faced before her.